2022
DOI: 10.3389/fphar.2022.839808
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Combination Therapy: A Strategy to Overcome Bacterial Resistance to Aminoglycoside Antibiotics

Abstract: After the first aminoglycoside antibiotic streptomycin being applied in clinical practice in the mid-1940s, aminoglycoside antibiotics (AGAs) are widely used to treat clinical bacterial infections and bacterial resistance to AGAs is increasing. The bacterial resistance to AGAs is owed to aminoglycoside modifying enzyme modification, active efflux pump gene overexpression and 16S rRNA ribosomal subunit methylation, leading to modification of AGAs’ structures and decreased concentration of drugs within bacteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 154 publications
2
59
0
Order By: Relevance
“…The spread and danger of multidrug-resistant infection force the medical community to rely on additional broad-spectrum antibiotics to cure these infections, leading to more resistance . This has become a concerning issue because of the limited options of antimicrobial agents currently available to fight against these pathogens. The lack of effective antibiotic options in the market is because of slow pace, high cost, and low selling prices of new antibiotics . Combination therapy can deal with and overcome antimicrobial resistance and repurpose existing antibiotics .…”
Section: Resultsmentioning
confidence: 99%
“…The spread and danger of multidrug-resistant infection force the medical community to rely on additional broad-spectrum antibiotics to cure these infections, leading to more resistance . This has become a concerning issue because of the limited options of antimicrobial agents currently available to fight against these pathogens. The lack of effective antibiotic options in the market is because of slow pace, high cost, and low selling prices of new antibiotics . Combination therapy can deal with and overcome antimicrobial resistance and repurpose existing antibiotics .…”
Section: Resultsmentioning
confidence: 99%
“…Although they have been used for several decades to treat infections caused by non-fastidious Gram-negative bacteria [ 30 ], the most prevalent bacterial resistance mechanisms in this antibiotic class are the enzymatic modification aminoglycoside antibiotics [ 31 ]. The enzymes belong to families, such as aminoglycoside phosphotransferases (APHs), aminoglycoside acetyltransferases (AACs), and aminoglycoside adenyl transferases (ANTs) [ 32 , 33 ]. These enzymes are often encoded on gene cassettes of integrons, also present in the isolates investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Here, K. pneumoniae (KP1) was resistant against ceftazidime, while gentamicin showed better activity but was not bactericidal against the isolate. It has been reported that β-lactams, such as ceftazidime, are known to break the bacterial cell wall in a non-fatal way, allowing aminoglycosides, such as gentamicin, to enter bacteria and increase their killing effectiveness [ 33 , 34 ]. In another study, aminoglycosides, due to their synergistic antibacterial properties, were combined with β-lactam antibiotics, which broadened the scope of treatment, accelerated bacterial clearance and enhanced antibiotic resistance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired 16S rRNA methyltransferase (16S-Rmtase) is one of the main mechanisms of aminoglycoside antibiotic resistance in bacteria. The enzyme uses S-adenosine methionine (SAM) as a cofactor to add methyl groups to specific residues of 16S rRNA ( Wang et al, 2022 ). AGs have a lower affinity for methylated 16S rRNA than for non-methylated 16S rRNA, which makes the bacteria resistant to a broad spectrum of AGs ( Wachino et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%